Brotherhood of Our Lady of Carmen of the Convent of San Bernardo (Salta, Argentina): Between tradition and modernity - Quinteros, Víctor Enrique (2021)
The first half of the 19th century was a period of decadence and decline for the colonial Salta religious brotherhoods. By then some of them had already disappeared, others survived decimated resources. In this scenario still marked by the turbulence of the revolutionary war, by the institutional weakness of independent governments and by the fragile existence of modern associations, the Brotherhood of Our Lady of Carmen was founded in the Convent of Carmelas Descalzas de Salta (Argentina). ). Through this article we intend to address its study, in the period between the middle and the last quarter of the nineteenth century, focusing our attention on the institutional guidelines that governed its operation and its imbrication and relationship with local society and its civil authorities. and ecclesiastical. A case study like the one proposed will allow us to observe the characteristics that these associative experiences assumed in the transition period from a regime of Christianity to one of religious modernity.